2016
DOI: 10.1158/0008-5472.can-15-0717
|View full text |Cite
|
Sign up to set email alerts
|

EPHA2 Blockade Overcomes Acquired Resistance to EGFR Kinase Inhibitors in Lung Cancer

Abstract: Despite the success of treating EGFR mutant lung cancer patients with EGFR tyrosine kinase inhibitors (TKIs), all patients eventually acquire resistance to these therapies. Although various resistance mechanisms have been described, there are currently no FDA-approved therapies that target alternative mechanisms to treat lung tumors with acquired resistance to first-line EGFR TKI agents. Here we found that EPHA2 is overexpressed in EGFR TKI resistant tumor cells. Loss of EPHA2 reduced the viability of erlotini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
92
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 50 publications
11
92
0
Order By: Relevance
“…This observation was in line with recent findings obtained in other studies demonstrating that EphA2 overexpression is involved in the resistance to both EGFR tirosin-kinase inhibitors (TKI) such erlotinib (lung cancer) (17) and vemurafenib (melanoma) (50) and moAbs as trastuzumab (breast cancer) (51). Additionally the EphA2 blockade is proposed as a new strategy to restore the anti-EGFR sensitivity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This observation was in line with recent findings obtained in other studies demonstrating that EphA2 overexpression is involved in the resistance to both EGFR tirosin-kinase inhibitors (TKI) such erlotinib (lung cancer) (17) and vemurafenib (melanoma) (50) and moAbs as trastuzumab (breast cancer) (51). Additionally the EphA2 blockade is proposed as a new strategy to restore the anti-EGFR sensitivity.…”
Section: Discussionsupporting
confidence: 91%
“…Notably adenocarcinoma EphA2 high tumor cells showed low expression levels both of Krt20 and Lgr5 along with an increased expression of Ascl2 suggesting that the EphA2 high cell population in tumors could represent a fraction of cells that underwent dedifferentiation and likely acquired CSC-like properties as supported by other studies in CRC, NSCLC and glioblastoma (17,39,40). We validated expression molecular results with the IHC analysis and we showed an overlap between EphB2+ cells and Lgr5+/Krt20− cells in normal mucosa.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…31) Amato et al compared EGFR TKI-sensitive with EGFR TKI-resistant EGFR-mutant lung cancer cell lines and determined that EphA2 Ser-897 and Tyr-588 phosphorylation as well as total EphA2 expression were markedly increased in the resistant cells. 65) Notably, EphA2 levels were higher in post-relapse tumor sections than in TKI-pretreatment tumor sections from four patients with the EGFR mutation. As expected, EphA2 knockdown reduced the cell viability of resistant cells in vitro.…”
Section: Cell Survival and Proliferationmentioning
confidence: 85%
“…EGFR-mutant NSCLC patients who benefited from EGFR-TKI eventually develop acquire resistance to these therapies [4, 19]. Although a number of studies revealed that a variety of mechanisms can stimulate acquired resistance to EGFR-TKI including secondary mutations within EGFR at position T790, mutation in EGFR effector proteins, small-cell lung cancer histologic transformation and upregulation of parallel receptor tyrosine kinases (e.g., MET, HER2 and AXL) [4], the mechanisms responsible for about 20–30% of cases of acquired resistance to EGFR-TKIs are still unknown.…”
Section: Discussionmentioning
confidence: 99%